Determinants of Farmers’ Income from Community Forestry in Nawalparasi, Nepal - Khanal, Badri (Journal of Agriculture and Environment, 2013)
Community forest has great impact on forest management but it has put a check on important component of family income of farmers who directly benefited from the forest. This was due to various factors affecting the forest income. This study analyzed the forest income determinants in community forestry in Nawalparasi District. Three community forests (Sundaree, Namuna women and Jharahi Plantation) were selected randomly. Ten explanatory variables were examined as determinants of share of gross forest income in gross family income of rural farmers using linear multiple regression analysis assuming all the explanatory variables are significantly related with gross family income. Four variables (economically active female, total land, percent of irrigated land and distance of forest) showed significant relationship with forest income. The paper suggests policy makers for taking proper attention to mainstream forest related programs, which are directly related to rural farmers income in policy formulation and implementation.